Bouveret’s Syndrome as a Rare Life-Threatening Complication of Gallstone Disease—A Surgical Problem: Two Case Reports - Nebojsa S. Ignjatovic; Ilija D. Golubovic; Miodrag N. Djordjevic; Marko M. Stojanovic; Daniela A. Benedeto Stojanov; Jelena S. Ignjatovic; Jelena D. Zivadinovic; Sonja Golubovic (Medicina)
Introduction: Bouveret syndrome, a rare and often underdiagnosed variant of gallstone ileus, is characterized by the presence of a large gallstone impacted in the proximal duodenum, resulting in significant gastric outlet obstruction and aerobilia. Early identification of Bouveret syndrome is crucial for developing an appropriate surgical strategy. Case 1: A 76-year-old female underwent a contrast-enhanced abdominal CT scan, which revealed a cholecysto-duodenal fistula with a 3.9 cm × 4.0 cm × 4.0 cm gallstone located in the proximal duodenum, along with a distended, fluid-filled stomach and aerobilia. Intraoperatively, due to chronic inflammation and adhesion between the gallbladder and duodenum, a cholecystectomy and fistula repair were performed. Case 2: A 72-year-old female presented with a gastroduodenal passage obstruction confirmed by imaging, which identified a duodeno-biliary fistula. The radiological examination showed oval filling defects in the duodenal bulb consistent with Bouveret’s syndrome, with the largest stone measuring approximately 6 cm in diameter. An enterotomy was performed for stone extraction and was followed by cholecystectomy and duodenal repair with omentoplasty. Conclusions: Bouveret’s syndrome is a rare but clinically significant condition that should be considered in patients presenting with signs of upper gastrointestinal obstruction, particularly in those with a history of chronic cholelithiasis. Early recognition and prompt surgical intervention are essential for obtaining optimal patient outcomes.